Designing the Short Film "Angel" as a Digital Da'wah Medium Relevant to Generation Z at Al-Hikam Islamic Boarding School Malang - Khoirul Mahmudi (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
This research was motivated by the phenomenon of the development of Islamic preaching in the digital era, which demands creative innovation in order to maintain the substance of Islamic teachings while attracting the attention of audiences, especially Generation Z. This research aims to design a short film entitled “Angel” as a digital medium for Islamic preaching that is relevant to Generation Z at the Al-Hikam Islamic Boarding School for Students in Malang. The method used is descriptive qualitative with a Research and Development (R&D) or media design approach. Data collection techniques included observation, interviews, documentation, and literature study. The resulting work was validated by subject matter experts and media experts, and tested on seven representatives of Generation Z. The results of the research and feasibility tests by the experts showed that the short film “Angel” was suitable for publication as a digital da'wah medium. Based on the results of the respondent interviews, this film is proven to be very relevant to the characteristics of Generation Z because it presents the conflicts of the reality of student life that are easy to understand and do not seem patronizing. It can be concluded that the short film “Angel” is effective as a means of digital da'wah that is subtle, relevant, and has the potential to be well internalized by Generation Z viewers.